1983
DOI: 10.1042/bj2150531
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the high-mobility-group chromosomal proteins in rainbow-trout (Salmo gairdnerii) liver and testis

Abstract: Chromatography and characterization of the proteins extracted by 5% (w/v) HClO4 from rainbow-trout (Salmo gairdnerii) liver and testis show that the two tissues present a characteristically different spectrum of high-mobility-group (HMG) proteins. A variant subfraction of HMG C is found in liver, but is not detectable in testis, where even the main fraction of HMG C is present in only very low quantity. A protein, F, which appears to be related to protein H6 has similarly been isolated only from liver and not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Since the electrophoretic patterns of liver HMG proteins shown in Fig. 5 were similar to those reported by Brown & Goodwin (1983), the HMG proteins were designated in accordance with the classification of these investigators. Liver contained HMG 14/17-like proteins D, C, H6 and F. G was a putative HMG protein.…”
Section: Characterization Of Histone Hlbmentioning
confidence: 64%
See 1 more Smart Citation
“…Since the electrophoretic patterns of liver HMG proteins shown in Fig. 5 were similar to those reported by Brown & Goodwin (1983), the HMG proteins were designated in accordance with the classification of these investigators. Liver contained HMG 14/17-like proteins D, C, H6 and F. G was a putative HMG protein.…”
Section: Characterization Of Histone Hlbmentioning
confidence: 64%
“…Rainbow-trout liver and testis chromatin are associated with HMG TI and T2, which are similar to HMG 1 and 2, and HMG H6, which is similar to HMG 14 and 17 (Brown et al, 1980;Rabbani et al, 1980;Christensen & Dixon, 1981;Brown & Goodwin, 1983). In addition to these HMG proteins, it has been reported that trout liver chromatin contains HMG proteins C, D and F, which were either absent or present at very low levels in testis (Brown & Goodwin, 1983). However, other investigators did not find these 'liver-specific' HMG proteins (Christensen & Dixon, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The main point of difference is the lower concentration of proline found in mouse LMG proteins, although this may be a species variation. Phylogenetic differences have been noted for HMG proteins (Christensen & Dixon, 1981;Brown & Goodwin, 1983). Among the LMG-like proteins we have isolated, it is noticeable that proteins PD6, PD8 and PD9 have a similar amino acid composition, Mr and electrophoretic mobility on polyacrylamide gels at pH 2.9.…”
Section: Discussionmentioning
confidence: 87%
“…They present strong evidence that PSI, PS2 and PS3 are not degradation products of HMG-14 and -17 but favour the view that they are variant forms of the latter proteins. Brown & Goodwin (1983) have also isolated genuine variants of trout testis HMG-14 and -17. We consider it likely that a similar situation holds for SC2 and SC3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation